2019
DOI: 10.1021/acs.jafc.9b01755
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Glutamate Dependence Mechanism for Poly-γ-glutamic Acid Production in Bacillus subtilis on the Basis of Transcriptome Analysis

Abstract: The development of commercial poly-γ-glutamic acid (γ-PGA) production by glutamate-dependent strains requires understanding the glutamate dependence mechanism in the strains. Here, we first systematically analyzed the response pattern of Bacillus subtilis to glutamate addition by comparative transcriptomics. Glutamate addition induced great changes in intracellular metabolite concentrations and significantly upregulated genes involved in the central metabolic pathways. Subsequent gene overexpression experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The genes encoding these proteins are also present in sodium. In B. subtilis natto, we found that the three ycg MNO genes are up-regulated in the co-production environment, which is consistent with the results in Bacillus subtilis (Sha Y et al, 2019). That may be the reason for the co-production of γ-PGA and NK simultaneously in soybean medium.…”
Section: Analysis Of Transcriptome Of B Subtilis Nattosupporting
confidence: 89%
See 2 more Smart Citations
“…The genes encoding these proteins are also present in sodium. In B. subtilis natto, we found that the three ycg MNO genes are up-regulated in the co-production environment, which is consistent with the results in Bacillus subtilis (Sha Y et al, 2019). That may be the reason for the co-production of γ-PGA and NK simultaneously in soybean medium.…”
Section: Analysis Of Transcriptome Of B Subtilis Nattosupporting
confidence: 89%
“…In this study, soybean was used as basic substrate for co-producing γ-PGA and nattokinase based on this phenomenon. Carbon sources and sodium glutamate which added to the substrates could improve γ-PGA and nattokinase production obviously (Zeng W et al, 2013;Sha Y et al, 2019). Wherein selecting sucrose as the carbon source based on the previous study that glucose, sucrose and fructose have similar effects on γ-PGA production (Shi F et al, 2006).…”
Section: Co-producing Of γ-Pga and Nattokinasementioning
confidence: 99%
See 1 more Smart Citation
“…We know that the gene cluster ( pgdS , pgsEACB ) involved in the synthesis γ-PGA are present in both strains B. velezensis 83 and B. velezensis FZB42 and they are of high identity (98%). Nevertheless, is known that B. velezensis 83 is a glutamic acid independent γ-PGA producing strain (Cristiano-Fajardo et al 2019 ) as other few Bacillus strains ( B. subtilis C10, Bacillus licheniformis A13, B. licheniformis TISTR 1010, B. methylotrophicus , B. subtilis NX2, B. amyloliquefaciens LL3) which only need glucose and NH 4 Cl as carbon and nitrogen sources, respectively, for γ-PGA synthesis (Cao et al 2011 ; Hsueh et al 2017 ; Sha et al 2019 ). In contrast, lack of γ-PGA production by B. velezensis FZB42 could be explained due to a glutamate dependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial synthetic pathway of γ-PGA principally covers three distinct stages: racemization, polymerization and transfer, and catabolism ( Figure 2 ) [ 10 , 11 , 22 ]. Glycolysis, the Pentose Phosphate Pathway (PPP), Tricarboxylic Acid (TCA) cycle, amino acid metabolism, and glutamate synthesis all participate in γ-PGA biosynthesis [ 56 ].…”
Section: Synthetic Pathway Of γ-Pgamentioning
confidence: 99%